2018
DOI: 10.1139/cjp-2017-0120
|View full text |Cite
|
Sign up to set email alerts
|

Physical proprieties of DC glow discharges in a neon–argon gas mixture

Abstract: This paper reports a detailed study of 90% Ne – 10% Ar gas mixture DC glow discharge at low pressure, wherein 15 chemical reactions are considered. The second-order fluid model is used. The parameters of particle transport and their rate coefficients strictly depend on mean electron energy. In the framework of the local electric field approximation, we have developed an analytical expression of the drift velocity of positive argon ions in a neon gas [Formula: see text], which is in good agreement with the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…Therefore, the production of argon ions is more efficient than of helium ions during the ionization process. This phenomenon is also observed in the case of Ne-Xe gas mixture [10], and Ne-Ar gas mixture [11]. To conclude, the current-voltage characteristics in 90%He-10%Ar gas mixture approach the current-voltage characteristics in pure argon gas for a certain range of the electric potential, which are shown in Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, the production of argon ions is more efficient than of helium ions during the ionization process. This phenomenon is also observed in the case of Ne-Xe gas mixture [10], and Ne-Ar gas mixture [11]. To conclude, the current-voltage characteristics in 90%He-10%Ar gas mixture approach the current-voltage characteristics in pure argon gas for a certain range of the electric potential, which are shown in Fig.…”
Section: Resultssupporting
confidence: 67%
“…In our previous research [9][10][11], we have found that the EEDF is non-Maxwellian for a threshold value of pressure, and again, it is related to the type of gas. The percentage of gas in the mixture is related to the ion mass.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Then, a description of the model is given by equations (1) to (25). Note that the difference between the existing model and the model given by [7,8] is devoted to the presence of both a and b percentages of the gas as well as the positive ion mobility of each gas in the mixture. The flux expressions of a particle are given as follows [22,23]: The gas ion mobility in the mixture is determined according to equation (22).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In the research papers [7][8][9][10], we find that the electron energy distribution function (EEDF) can be Maxwellian at a very low pressure, and is related to the type of gas. The EEDF is non-Maxwellian for a threshold pressure value, and is again related to the type of gas.…”
Section: Introductionmentioning
confidence: 99%